Oil Sector of Russia: Current Situation and Trends - M. Beltyukova, S.; P. Pazdnikova, N.; V. Karpovich, Yu.; A. Kuznetsov, P.; ., . (International Journal of Engineering and Technology, 2018)
The article reviews practical experience and some theoretical aspects of the functioning of the oil sector in the Russian economy, analyzes the current situation in the large oil and gas fields of the Russian Federation, reveals negative and positive factors regarding the development of the oil sector in the national economy. Expert assessments of the state and prospects for the oil sector development are given based on the results of the analysis of its main indicators.Â Â